Nonporous MOF-derived dopant-free mesoporous carbon as an efficient metal-free electrocatalyst for the oxygen reduction reaction. Issue 24 (1st June 2016) - Wang, Xin; Li, Xingyue; Ouyang, Canbin; Li, Zhen; Dou, Shuo; Ma, Zhaoling; Tao, Li; Huo, Jia; Wang, Shuangyin
Abstract : Dopant-/metal-free mesoporous carbon has been prepared from nonporous MOFs, which is highly efficient for the electrocatalytic oxygen reduction reaction (ORR). The excellent ORR activity is attributed to both high specific surface area and mesoporous structure. Abstract : In this work, we report the synthesis of mesoporous carbon derived from nonporous MOFs without any heteroatom doping or residual metal, which is highly efficient for the electrocatalytic oxygen reduction reaction. The excellent ORR activity is attributed to both high specific surface area and mesoporous structure.